A research on mobbing behaviors football trainers face in club environment - Fatih Yenel; Hakan Sunay; Recep Cengız (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to determine the perceptions of football trainers about mobbing according to their age groups, license types, graduation levels and training years. In this research, the Negative Acts Questionnaire (NAQ), which was developed by Einarsen, Raknes, Matthiesen and Hellesoy, adapted to Turkish by Cemaloğlu (6), applied to 754 trainers participating in the seminars within the cities of Ankara, Batman, Denizli, Diyarbakır, Elazığ, Gaziantep, Mardin, Tokat and Samsun whichin the trainer development seminars were organized jointly by the Turkish Football Federation and Turkish Football Coaches Association in 2010-2011. The missing and faulty questionnaires were excluded from the study, and 515 ones were evaluated. The data from the questionnaire were analyzed by the reliability analysis and the non-parametric variance analysis. There were statistically significant differences in the sub-dimensions of the negative acts scale between their age groups for football trainers (p lt;0.05). By the statistical analysis, the youngest age group (19-29) of football trainers was subjected to negative acts much more than the other age groups were detected. On the other hand, the perceptions of mobbing for football trainers were not significantly different in terms of their training years and graduation levels (p gt;0.05).           As a result, it is possible to say that if sportive expectations are not met in football clubs, the pressures of football club managers, media or supporters may negatively affect on football trainers. Hence, the research findings show that the behaviors of mobbing can be evaluated as features peculiar to football, and mostly the youngest trainers are influenced by this situation.